Analisis Penggunaan Gaya Bahasa Perbandingan Pada Puisi Karya William Blake - Futri Mega Rahayu; Arif Triyuono (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
The purpose of this research is to analyze and identify the dominant types of figurative language in nine selected poems by William Blake. In this research, the author uses the library method. The theory utilized for analyzing Blake's poems is Tarigan's theory, which categorizes figurative language into four groups, but the author limits the analysis to only one group of figurative language comparison (Simile, Metaphor, Personification, Depersonification, Antithesis, Allegory, and Pleonasm). The author finds the total data, 2 instances or 5% contain similes, 7 instances or 17.5% contain metaphors, 16 instances or 40% contain personification, 0 instances or 0% contain depersonification, 10 instances or 25% contain antithesis, 3 instances or 7.5% contain allegory, and 2 instances or 5% contain pleonasm. Therefore, it can be concluded that the most dominant type of comparative language in Blake's poetry is personification.